Influenza Infections and Emergent Viral Infections in Intensive Care Unit - Cantan, Ben; Luyt, Charles-Edouard; Martin-Loeches, Ignacio (Seminars in Respiratory and Critical Care Medicine, 2019)
Critically ill patients are admitted to an intensive care unit (ICU) for multiple reasons. In this study, we aim to analyze the current evidence and findings associated with influenza and other emergent viral infections, namely, herpes simplex virus type 1 (HSV-1), Epstein-Barr virus (EBV), and cytomegalovirus (CMV).Among medical conditions, community-acquired respiratory infections are the most frequent reason for ventilatory support in ICUs. Community-acquired pneumonia in a severe form including the need of invasive mechanical ventilation and/or vasopressors is associated with high mortality rates. However, after the pandemic that occurred in 2009 by H1N1 influenza, the number of cases being admitted to ICUs with viral infections is on the rise. Patients in whom an etiology would not have been identified in the past are currently being tested with more sensitive viral molecular diagnostic tools, and patients being admitted to ICUs have more preexisting medical conditions that can predispose to viral infections. Viral infections can trigger the dysregulation of the immune system by inducing a massive cytokine response. This cytokine storm can cause endothelial damage and dysfunction, deregulation of coagulation, and, consequently, alteration of microvascular permeability, tissue edema, and shock. In severe influenza, this vascular hyperpermeability can lead to acute lung injury, multiorgan failure, and encephalopathy. In immunocompetent patients, the most common viral infections are respiratory, and influenza should be considered in patients with severe respiratory failure being admitted to ICU. Seasonality and coinfection are two important features when considering influenza as a pathogen in critically ill patients.Herpesviridae (HSV, CMV, and EBV) may reactivate in ICU patients, and their reactivation is associated with morbidity/mortality. However, whether a specific treatment may impact on outcome remains to be determined.
Keywords: community-acquired respiratory infections; herpesviridae; intensive care unit